Meta-analysis of a controlled study of levosimendan combined with Sacubitril/Valsartan for the treatment of heart failure with reduced ejection fraction in China - Li, Che; Zheng, Jifeng; Zhang, Bin; Xu, Jianjiang; Chu, Zhenliang (Frontiers in Cardiovascular Medicine, 2024)
Objective Levosimendan and Sacubitril/Valsartan are both potent pharmacotherapeutic agents in the clinical management of heart failure characterized by reduced ejection fraction. However, the limited efficacy of monotherapy and the lack of extensive clinical experience with combination therapy necessitate further investigation. This study aimed to evaluate the therapeutic effects of combining levosimendan with sacubitril/valsartan on chronic heart failure with reduced ejection fraction, specifically through a meta-analysis of studies conducted in China. Methods Cochrane systematic evaluation method was used to complete data retrieval from the following related databases: (1) Wanfang database; (2) CNKI China Academic Journal Network; (3) Wipo Full-text Database of Chinese Sci-tech journals; (4) PubMed; (5) Medline; (6) Chinese Biomedical Literature Database; (7) Web of Science; and (8) Google Scholar database. We searched for studies published up to December 2021. Data were extracted from applicable articles. Meta-analyses were performed to assess the left ventricular ejection fractions (LVEF) level, NT-proBNP level, Clinical efficacy, and the left ventricular end-diastolic dimension (LVEDD) level outcomes, following PRISMA 2020 guidelines. Results A total of five randomized controlled trials (RCTs) comprising 398 patients were included, half of the patients for levosimendan combined with Sacubitril/Valsartan and half of the patients for control groups. The effective rate in experimental group was significantly higher than that in control group [Peto-OR = 3.08, 95% CI (1.83, 5.19), P < 0.05]. The LVEF level after treatment in the experimental group was significantly higher than that in the control group [MD = 5.51, 95% CI (4.25, 6.76), P < 0.05]. After treatment, the LVEDD level in the experimental group was lower than that in the control group [MD = −3.83, 95% CI (−7.60, −0.05), P < 0.05]. There was a statistically significant difference in the N terminal pro B type natriuretic peptide (NT-proBNP) level between the two groups after treatment, where the value for the experimental group was lower than that for the control group [SMD = −2.68, 95% CI (−3.94, −1.43), P < 0.05]. Conclusion Meta-analysis results showed that levosimendan combined with Sacubitril/Valsartan has a better therapeutic effect on heart failure with reduced ejection fraction and is beneficial for improving cardiac function. The main mechanism for this may be related to the pharmacological action of levosimendan.